Perubahan Struktural Fungsional Prostitusi Online dalam Pandangan Talcott Parsons - Zainal Fadri (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
Online prostitution was uncovered after it was discovered that several social media accounts provided sex services that were easily accessible and at varying prices. The emergence of online prostitution has been reported as a form of resistance by some prostitutes in getting customers due to the closure of many localized places as centers of sexual transactions. Far from that, online prostitution has a troubling impact on the local community, especially for young people who are still at puberty, many of whom have fallen into the form of prostitution. This paper highlights the functional changes of prostitution that are offered with internet access and social media as functional changes in prostitution relations so that efforts are made to find the root of the problem in online prostitution. The method used in this writing is descriptive qualitative, namely by reading the supporting literature and by following the news about the development of online prostitution. The results obtained are that online prostitution is not pure prostitution for economic reasons, but rather refers to the concept of trends and lifestyles, so that the changes seen in online prostitution are structural changes in prostitution as well as irregularities in prostitution behavior that can be said as deviant behavior or pathological behavior.